Serodiagnosis of visceral and cutaneous leishmaniasis in human and canine populations living in Indigenous Reserves in the Brazilian Amazon Region - Ribeiro de Lima, Julia Teresa; Gennari, Solange Maria; Soares, Herbert Sousa; Hamad Minervino, Antonio Humberto; Malheiros, Antonio Francisco; Marques, Fernando Silveira; Laurenti, Myrcia Dalastra; Machado, Rosangela Zacarias [UNESP]; Marcili, Arlei; Labruna, Marcelo Bahia; Soares, Rodrigo Martins (Soc Brasileira Medicina Tropical, 2017)
Introduction: Leishmaniasis is endemic to the Northern, Northeastern, Central-Western, and Southeastern regions of Brazil. We aimed to assess the epidemiological situation of leishmaniasis in humans and dogs in indigenous villages located in the States of Mato Grosso and Tocantins using a serological survey conducted in May 2011. Methods: Serum samples were collected from 470 humans and 327 dogs living in villages of the Urubu Branco and Tapirape Karaja indigenous reserves. The samples were analyzed for the presence of Leishmania spp. antibodies using the indirect fluorescent antibody test (IFAT), enzymelinked immunosorbent assay (ELISA) with a crude antigen (CA) and soluble antigen (SA), and Dual Path Platform (DPP (R)) immunoassay for canine visceral leishmaniasis. Results: Of 470 human samples tested, two (0.4%) were positive using IFAT. Among 327 dog samples tested, 28 (8.6%) were positive using ELISA CA, five (1.5%) using ELISA SA, two (0.6%) using IFAT, and none using DPP (R) immunoassay with Leishmania infantum chagasi antigen. When Leishmania amazonensis antigen was used, 20 (6.1%) samples were positive using ELISA CA and four (1.2%) using IFAT. Conclusions: There was a low prevalence of infection in the region, and significant differences among the main serological methods used for the diagnosis of leishmaniasis. These findings indicated that the detection of Leishmania spp. requires further study and improvement.
Keywords: Trypanosomatid; Zoonosis; Reservoirs; Diagnosis; Indigenous